In Silico Evaluation Of Eugenol As A Potential Antifungal Agent: Targeting Beta-Glucocerebrosidase And Cyp51 - Anoosha, Anoosha; Prabhu K, Prabhu K; CS, Janaki; Bindu D, Bindu D; Fathimaa S, Refa; Basavaraj Rudagi, Khushi (Journal of Neonatal Surgery, 2025)
Fungal infections pose a significant health risk, with a growing concern for drug-resistant strains. This study investigates the potential of Eugenol (PubChem ID: 3314), a natural compound, as an antifungal agent through molecular docking analysis. The research targets three key fungal virulence proteins: beta-glucocerebrosidase (9FA3), Demethylase (6UEZ), and Upc2 (7VPU), utilizing AutoDock 1.5.7 to evaluate binding affinities and molecular interactions. Eugenol exhibited the strongest binding affinity for beta-glucocerebrosidase (−5.76 kcal/mol, 59.89 µM), where it formed crucial hydrogen bonds with residues SER-77 and TYR-79, indicating a strong potential for enzymatic inhibition. For Demethylase, Eugenol’s binding affinity was −5.53 kcal/mol (88.85 µM), suggesting moderate potential in disrupting fungal cell metabolism. In the case of Upc2, Eugenol displayed a slightly lower affinity (−4.99 kcal/mol, 219.20 µM), yet still indicated possible interactions that could interfere with fungal sterol regulation. These findings highlight Eugenol’s promising multi-target antifungal activity, particularly against key fungal enzymes involved in virulence and metabolic processes. The results suggest that Eugenol may be a viable candidate for further experimental investigation as a natural antifungal agent. Future in vitro and in vivo studies are necessary to confirm these computational predictions and explore the broader therapeutic potential of Eugenol in treating fungal infections.